Examining the relationship between IELTS preparation and English language proficiency skills of international students - Maryam, Zahra; Rehman, Asad Ur; Nawal, Ayesha; Shoaib, Muhammad; Ullah, Ihtisham (Journal of International Students, 2025)
IELTS is a widely accepted English language proficiency test, required for academic and professional purposes. In this study, we examined the relationship between IELTS and the English proficiency skills of international students. We developed a proximal mediation model based on Bandura’s triadic reciprocal determinism theory and tested it using covariance-based structural equation modeling. Data were collected through a survey of 275 international students preparing for IELTS to meet their academic requirements. The students reported that IELTS assessments significantly improved their English skills. They reported positive views of IELTS as an exam to enhance their language proficiency. Learning motivation for self-regulated learning and perceived self-efficacy for academic achievement served as two mediating factors that positively influenced the relationship between students’ perceptions of IELTS and their English skills. Finally, the study analyzed the moderating effects of students’ time management skills and found significant positive moderating effects.